Microstructure and magnetic properties of as-cast Ni2MnGa rods and tubes solidified by suction casting - Pozo Lopez, Gabriela del Valle (2019)
Ni2MnGa cylinders and tubes are solidified in water chilled copper molds, a few millimeters in external diameter and 5 cm long, by the suction casting technique. At room temperature, all samples are in cubic austenitic phase. Microstructure and crystallographic texture of the as-cast rods and tubes are characterized by XRD, SEM, EBSD and TEM. Because of the heat extraction geometry samples exhibit a strong texture, with the [100] direction preferentially oriented in the radial direction, together with a random distribution on the long axis. This texture is more marked in the tubes. XRD and TEM results indicate that the major austenitic phase is fcc, with L21 order. A minority volume of the equilibrium B2′ disordered phase is detected by the presence of two close Curie temperatures in cylinders and tubes 2 mm in external diameter, but not when this diameter is near 1 mm. Precipitates of the stable compounds α-Mn(S,Se), with a NaCl-type structure, and monoclinic P4S5 are observed in all the samples. Cylinders and tubes in austenitic phase are magnetically soft. Hysteresis loops in martensitic phase exhibit local steps associated to a magnetization mechanism involving twin boundary displacement, indicating that a field-induced variant reordering takes place. The switching field Hsw, corresponding to the magnetization step observed, is identified as the field at which twin boundaries become mobile. The measured values of 0.37 T–0.49 T are consistent with those corresponding to the onset of Type I twin boundaries displacement in 5 M martensite, with an equivalent threshold stress of 1 MP.